Noun and verb codes in pedagogical dictionaries of English: User-friendliness revisited - Dziemianko, Anna (Universitat Pompeu Fabra, 2008)
The aim of the present paper is to assess the user-friendliness of noun and verb coding systems in pedagogical dictionaries of English, measured by the frequency with which relevant information properly used in a productive task is located in codes. The influence of the following independent variables on the user-friendliness of codes is studied: the degree of syntactic congruity between Polish lexical items and English headwords, the form of codes, the grammatical category of headwords and the level of dictionary users’ proficiency in English. To investigate the influence of the form of codes on their user-friendliness, codes in noun and verb entries were divided into mainstream – referring to formal categories, transparent and prevalent in pedagogical dictionaries, and alternative – which, used very sparingly in today’s dictionaries, include reference to sentence functions (verbs) or many quite opaque symbols (nouns).Conclusions are drawn on the basis of an experiment in which almost 900 Polish subjects, advanced and intermediate in English, were involved in a translation task in which they had to use English noun and verb entries compiled for the purpose of the study. The results show that differences in grammar between Polish and English did not affect the consultation of either noun or verb codes. Strangely enough, alternative, and seemingly more demanding codes were strongly favored by the intermediate subjects, and – in the case of verbs – also the advanced ones. The part of speech played a very significant role at the higher level of proficiency, but was not important for the reference to codes by the less advanced. Finally, the higher level of proficiency in English made the subjects appreciate codes more fully, which may be seen as an argument for maintaining the over 70-year tradition of encoding syntactic information in pedagogical dictionaries of English.
Keywords: Syntax; Codes; Dictionary; User-friendliness